Jump and change of direction speed asymmetry using smartphone apps: between-session consistency and associations with physical performance - Bishop, C.; Perez-Higueras Rubio, M.; Gullon, I. L.; Maloney, S.; Balsalobre-Fernandez, C. (The Journal of Strength and Conditioning Research, 2022)
The aims of this study were to (a) quantify the magnitude and direction of asymmetry from jump and change of direction speed (CODS) tests and (b) determine the relationship between these asymmetries and jump and CODS performance, in a test-retest design. Thirty Spanish national-level youth basketball athletes performed single leg countermovement jumps (SLCMJs), single leg drop jumps (SLDJs), and 505 CODS tests, all assessed using the My Jump 2 and CODTimer smartphone applications. All tests showed good to excellent reliability, with no significant differences identified between test sessions in jump, CODS, or asymmetry data. The direction of asymmetry showed substantial levels of agreement between test sessions for jump height during the SLDJ (Kappa = 0.72), but only fair levels of agreement for reactive strength during the SLDJ (Kappa = 0.25), fair levels of agreement for jump height during the SLCMJ (Kappa = 0.29), and slight levels of agreement for total time during the 505 test (Kappa = 0.18). Jump height asymmetry from the SLDJ was significantly associated with reduced jump height (p = -0.44), reactive strength (p = -0.46) and 505 times (p = 0.45-0.48) in test session 1, and reactive strength (p = -0.42) and 505 times (p = 0.40) in test session 2. These data show that jump height asymmetry from the SLDJ was associated with reduced jump and CODS performance in youth basketball athletes during repeated test sessions. In addition, the same asymmetry metric was the only one to show substantial levels of agreement between test sessions. Owing to the consistency of these data, SLDJ height asymmetry may be a useful metric to measure when monitoring interlimb asymmetries.